Evaluating instrumented Charpy impact strain signals using curve fitting equations - Ali, Mohd Basri; Abdullah, Shahrum (Springer, 2014)
An effective and simple way to develop equations from impact strain signals was proposed. Little research has been performed in this area, but this equation is very important for evaluating input signals in finite element analysis impact tests and for obtaining additional information on material deformation and fracture processes under impact loading. For this purpose, dynamic impact responses were examined through signals obtained from a strain gauge installed on an impact striker connected to a data acquisition system. Aluminium 6061-T6 was used to extract strain responses on the striker during Charpy impact testing. Statistical analysis was performed using the I-kaz method, and curve fitting equations based on the equation for vibration response under a non-periodic force were used to evaluate the Charpy impact signals. The I-kaz coefficients and curve fitting equations were then compared and discussed with related parameters, such as velocities and thicknesses. Velocity and thickness were found to be related to the strain signal patterns, curve fitting equations and I-kaz coefficients. The equations developed using this method had R2 values greater than 97.7%. Finally, the constructed equations were determined to be suitable for evaluating Charpy impact strain signal patterns and obtaining additional information on fracture processes under impact loading.